Kedudukan Hukum Pengguna Prompt dalam Karya Visual Berbasis Artificial Intelligence Generatif Perspektif Hukum Hak Cipta Indonesia - Hamid, Amrullah; Selamat Lumban Gaol; Rizky Pratama Putra Karo Karo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the legal status of prompt users in generative AI-based visual works and examine the form of copyright legal protection for these works from an Indonesian legal perspective. The study uses a normative legal research method with a statutory, conceptual, and comparative approach. The results of the study indicate that Law Number 28 of 2014 concerning Copyright still adheres to the Human Authorship doctrine which places humans as the sole legal subject of the creator. However, prompt users can be qualified as creators if they are proven to have made a substantive creative contribution to the visual works produced by the generative AI system. This study also found a gap in legal norms related to the regulation of AI-based works in Indonesia, so that a reformulation of copyright regulations that are adaptive to the development of digital technology is needed. The conclusion of this study is that copyright regulations in Indonesia are still based on the Human Authorship doctrine, so that generative AI has not been recognized as creators, while prompt users can be recognized as creators if they make a substantive creative contribution, so that a reformulation of the Copyright Law is needed to address the gap in norms and provide legal certainty for works produced with the help of generative AI. Keywords: Copyright, Generative Artificial Intelligence, Legal Subject, User Prompt, Visual Artwork.